Women's Labor Market Responses to Their Partners' Unemployment and Low-Pay Employment - Carina Keldenich; Andreas Knabe (Journal of Labor Research, 2022)
Using bivariate random-effects probit estimation on data from the German Socio-Economic Panel we show that women respond to their partners' unemployment with an increase in labor market participation, which also leads to an increase in their employment probability. Our analysis considers within and between effects separately, revealing differences in the relationships between women's labor market statuses and their partners' unemployment in the previous period (within effect) and their partners' overall probability of being unemployed (between effect). Furthermore, we contribute to the literature by demonstrating that a partner's employment in a low-paid job has an effect on women's labor market choices and outcomes similar to that of his unemployment.
Keywords: D12; D13; J22; 330; Added worker effect; Labor supply; Family economics; Unemployment; Low-pay employment